Moral As A Medium Of Islamic Education - Dita Yuliana Sahpitri; Rifa Dalillah (Proceeding International Seminar of Islamic Studies, 2019)
This research is entitled morality as an Islamic education media. the problem that arises is the large number of students who are still lacking in ethics towards educators in the education institution. how to make morality as an Islamic education?. The purpose of this study is to improve the morals of students towards educators. the method used is labrary research, qualitative. it was found that the educational tool was a variety of sessions according to the needs of students. the basis used in describing learning ethics emphasizes Islamic ethics, so that the reference sources used are the Qur'an and Sunnah as well as the opinions of the scholars who concentrate on Islamic education. at the vertex that ethics or morals in Islam is the most effective way of transferring knowledge to students.